The Role of Legal Assistance in Preventing Property Business Disputes in Gunungkidul Yogyakarta Indonesia - Zaenal Mustofa; Zaid Haziq Abdullah bin Sulaeman (Eastasouth Journal of Positive Community Services, 2026)
This community service aims to implement legal assistance as an effort to prevent property business disputes in Indonesia, with activities located in Gunung Kidul Regency, Yogyakarta. The background of this community service is based on the low level of public understanding of the legal aspects of property business, particularly land legality, agreements, and dispute resolution mechanisms. The method used is a participatory qualitative approach through a community legal empowerment model, which is implemented through problem identification, legal counselling, participatory discussions, direct legal assistance, and activity evaluation. The results of the community service programme showed an increase in the community's legal understanding and awareness, as well as a change in attitude towards conducting property business transactions in a more careful and legally compliant manner. Legal assistance proved to play a strategic role as a preventive instrument in preventing disputes, strengthening legal culture, and supporting sustainable local economic development.